Lagenaria siceraria fruit: A review of its phytochemistry, pharmacology, and promising traditional uses - Saeed, Muhammad; Khan, Muhammad Sajjad; Amir, Kinza; Bi, Jannat Bi; Asif, Muhammad; Madni, Asadullah; Kamboh, Asghar Ali; Manzoor, Zahid; Younas, Umair; Chao, Sun (Frontiers in Nutrition, 2022)
Since ancient times, the Cucurbitaceae family is used as a therapeutic option in human medicine. This family has around 130 genera and 800 species. Researchers have studied the various plants of this family including Lagenaria siceraria due to their medicinal potential. Various properties are beneficial for human health, that have been attributed to L. siceraria like antioxidant, hypolipidemic, diuretic, laxative, hepatoprotective, analgesic, antihypertensive, cardioprotective, central nervous system stimulant, anthelmintic, free radical scavenging, immunosuppressive, and adaptogenic. The fruit of this plant is commonly used as a vegetable that has a low-calorie value. The species possess a diverse set of biological compounds like flavonoids, sterols, saponins, and terpenoids. Vitamins, choline, flavonoids, minerals, proteins, terpenoids, and other phytochemicals are also found in the edible parts of this plant. Besides 17 different amino acids, many minerals are reported to be present in the seeds of L. siceraria. According to the USDA nutritional database per 100 g of L. siceraria contains 14 Kcal energy, 3.39 g carbohydrates, 0.62 g protein, 0.2 g fat, and 0.5 g fiber. L. siceraria performs a wide range of pharmacological and physiological actions. The literature reviewed from various sources including PubMed, Science Direct, Google scholar, etc. shows the remarkable potential to treat various human and animal illnesses due to its' potent bioactive chemicals. The key objective of this thorough analysis is to present a summary of the data about the beneficial and harmful effects of L. siceraria intake on human health, as well as in veterinary fields.